COMMUNITY CAPACITY BUILDING IN PUBLIC ORDER AND PUBLIC ORDER IN AMPENAN DISTRICT, MATARAM CITY - Syaefullah; Dwi Putri Yuliani; Wiredarme; Muh. Suhardi; Abdul Wahab; Abdul Rahman; Luh Putu Vera Astri; M.Zaki Taufik (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This Community Service (PKM) aims to increase understanding, legal awareness, and community capacity in maintaining public order and public peace, as well as community protection (Trantibumlinmas) in Ampenan District, Mataram City. The background to this activity is based on the still low level of public understanding of regulations, the less than optimal role of the Community Protection Unit (Satlinmas), and the lack of community participation in maintaining environmental security, especially in heterogeneous communities such as immigrant communities. The activity implementation method uses a participatory and educational approach through socialization, interactive discussions, community mentoring, and activity evaluation. Data collection techniques are carried out through observation, interviews, documentation, and literature studies. This activity involves the community, village officials, community leaders, youth, and Satlinmas members as the main actors in the implementation of Trantibumlinmas. The results of the activity show an increase in community understanding of the Minister of Home Affairs Regulation Number 26 of 2020, increased legal awareness, and growing community participation in maintaining environmental order. In addition, the role of Satlinmas also shows improvements in aspects of early detection, environmental security, and social mediation at the village level. Thus, this Community Service Program (PKM) activity contributes to strengthening the synergy between the community, government, and the Public Order Agency (Satlinmas) in creating a safe, orderly, and conducive environment. The resulting recommendations include the need for continuous strengthening of the capacity of the Public Order Agency (Linmas) and an enhanced community-based participant approach to the implementation of the Public Order Agency (Trantibumlinmas).